CD38 Ligation in Peripheral Blood Mononuclear Cells of Myeloma Patients Induces Release of Protumorigenic IL-6 and Impaired Secretion of IFNγ Cytokines and Proliferation - Giorgio Fedele; Marco Di Girolamo; Umberto Recine; Raffaella Palazzo; Francesca Urbani; Alberto L. Horenstein; Fabio Malavasi; Clara Maria Ausiello (Mediators of Inflammation)
CD38, a surface receptor that controls signals in immunocompetent cells, is densely expressed by cells of multiple myeloma (MM). The immune system of MM patients appears as functionally impaired, with qualitative and quantitative defects in T cell immune responses. This work answers the issue whether CD38 plays a role in the impairment of T lymphocyte response. To this aim, we analyzed the signals implemented by monoclonal antibodies (mAb) ligation in peripheral blood mononuclear cells (PBMC) obtained from MM patients and compared to benign monoclonal gammopathy of undetermined significance (MGUS). PBMC from MM both failed to proliferate and secrete IFNγ induced by CD38 ligation while it retained the ability to respond to TCR/CD3. The impaired CD38-dependent proliferative response likely reflects an arrest in the progression of cell cycle, as indicated by the reduced expression of PCNA. CD38 signaling showed an enhanced ability to induce IL-6 secretion. PBMC from MM patients displays a deregulated response possibly due to defects of CD38 activation pathways and CD38 may be functionally involved in the progression of this pathology via the secretion of high levels of IL-6 that protects neoplastic cells from apoptosis.